1987
DOI: 10.1093/mutage/2.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Very low doses of X-rays can cause human lymphocytes to become less susceptible to ionizing radiation

Abstract: Cultured human lymphocytes exposed to very low doses of X-rays become less susceptible to subsequent higher doses of X-rays. Cells exposed to doses as low as 0.5 rad (cGy) or 1 rad of X-rays at 32-34 h of culture become adapted so that less cytogenetic damage in the form of chromosome breakage is induced by 150 rad administered at 48 h. This response, which does not occur after high initial doses of X-rays, can be eliminated by 3-aminobenzamide, an inhibitor of poly(ADP-ribose) polymerase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(77 citation statements)
references
References 8 publications
5
72
0
Order By: Relevance
“…A similar difference, with and without 3AB treatment, is also observed in the case of challenge with 1.5 Gy X-rays: 15 -14% as compared with 59-52%. These results suggest that the addition of 3AB negates the adaptation response in human lymphocytes and support the observations made by Wiencke et al (1986) and Shadley et al (1987). However, the magnitude of reduction in the adaptation response by 3 AB is greater in the case of challenge with X-rays as compared with BLM.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A similar difference, with and without 3AB treatment, is also observed in the case of challenge with 1.5 Gy X-rays: 15 -14% as compared with 59-52%. These results suggest that the addition of 3AB negates the adaptation response in human lymphocytes and support the observations made by Wiencke et al (1986) and Shadley et al (1987). However, the magnitude of reduction in the adaptation response by 3 AB is greater in the case of challenge with X-rays as compared with BLM.…”
Section: Resultssupporting
confidence: 88%
“…(1984) first reported that prior exposure of human lymphocytes to low levels of radioactive thymidine ( 3 [H]dThd) led to a significant reduction in the chromosome damage induced by a subsequent high dose of X-rays. Shadley and Wolff (1987) also observed that an X-ray dose, as low as 0.01 Gy, can protect the lymphocytes against the cytogenetic damage induced by a subsequent exposure to 1.5 Gy X-rays. The radiation dose used for adaptation seemed to have an effect; so also the time-interval between the adaptation and challenge doses (Shadley etal., 1987), the dose rate and the quality of radiation (Wiencke et al, 1987).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, we found 4 dicentrics among control subjects and 2 among technicians (Table 4). It could be hypothesized that the higher number of dicentrics found in the control group was the result of an unknown exposure of these subjects to environmental xenobiotics and/or of a higher capacity of the technicians, chronically exposed to low doses of IR, to induce apoptosis in cells carrying severe chromosomal damages as a mechanism of individual adaptive response (Shadley and Wolff, 1987;Vijayalaxmi et al, 1995;Ikushima et al, 1996). The frequency of CAs serves as the most reliable biological exposure marker in case of acute accidental radiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, using varying biological endpoints (e.g., chromosomal damage, mutations, neoplastic transformation, and cancer), beneficial (not detrimental) effects of exposure to low doses of radiation have been found (Luckey 1982;Shadley and Wolff 1987;Bond et al 1991;Luckey 1991;Cohen 1995;Azzam et al 1996;Mitchel et al 1999;Calabrese and Baldwin 2000;Hooker et al 2004;Elmore et al 2005;Feinendegen 2005;Day et al 2006;Tubiana et al 2006;Feinendegen et al 2007). Nonetheless, information on such benefits is mainly limited to low doses of low linear-energy-transfer (LET) photons (i.e., X and γ rays) or combinations of low-LET gamma and high-LET alpha radiation (Scott nents to the dose (protons, neutrons, other ions) were 99%, 99%, 98%, 94%, and 94% respectively.…”
Section: Introductionmentioning
confidence: 99%